Noval Dual-Emission Fluorescence Carbon Dots as a Ratiometric Probe for Cu2+ and ClO− Detection - Jiaqing Guo; Aikun Liu; Yutian Zeng; Haojie Cai; Shuai Ye; Hao Li; Wei Yan; Feifan Zhou; Jun Song; Junle Qu (Nanomaterials, 2021)
The use of carbon dots (CDs) with dual emission based on ratiometric fluorescence has been attracting attention in recent times for more accurate ion detection since they help avoid interference from background noise, probe concentration, and complexity. Herein, novel dual-emission nitrogen-doped CDs (NCDs) were prepared by a simple method for Cu2+ and ClO- detection. The NCDs showed excellent anti-interference ability and selectivity for different emissions. In addition, a good linear relationship was observed between the fluorescence intensity (FI) of the NCD solutions in different emissions with Cu2+ (0–90 μM) and ClO− (0–75 μM). The limits of both Cu2+ detection and ClO− were very low, at 17.7 and 11.6 nM, respectively. The NCDs developed herein also showed a good recovery rate in water for Cu2+ and ClO− detection. Hence, they are expected to have a more extensive application prospect in real samples.